Increased cardiac Pi/PCr in the diabetic heart observed using phosphorus magnetic resonance spectroscopy at 7T - Valkovič, L; Apps, A; Ellis, J; Neubauer, S; Tyler, DJ; Schmid, AI; Rider, OJ; Rodgers, CT (Public Library of Science, 2022)
Phosphorus magnetic resonance spectroscopy (31P-MRS) has previously demonstrated decreased energy reserves in the form of phosphocreatine to adenosine-tri-phosphate ratio (PCr/ATP) in the hearts of patients with type 2 diabetes (T2DM). Recent 31P-MRS techniques using 7T systems, e.g. long mixing time stimulated echo acquisition mode (STEAM), allow deeper insight into cardiac metabolism through assessment of inorganic phosphate (Pi) content and myocardial pH, which play pivotal roles in energy production in the heart. Therefore, we aimed to further explore the cardiac metabolic phenotype in T2DM using STEAM at 7T. Seventeen patients with T2DM and twenty-three healthy controls were recruited and their cardiac PCr/ATP, Pi/PCr and pH were assessed at 7T. Diastolic function of all patients with T2DM was assessed using echocardiography to investigate the relationship between diastolic dysfunction and cardiac metabolism. Mirroring the decreased PCr/ATP (1.70±0.31 vs. 2.07±0.39; p<0.01), the cardiac Pi/PCr was increased (0.13±0.07 vs. 0.10±0.03; p = 0.02) in T2DM patients in comparison to healthy controls. Myocardial pH was not significantly different between the groups (7.14±0.12 vs. 7.10±0.12; p = 0.31). There was a negative correlation between PCr/ATP and diastolic function (R2 = 0.33; p = 0.02) in T2DM. No correlation was observed between diastolic function and Pi/PCr and (R2 = 0.16; p = 0.21). In addition, we did not observe any correlation between cardiac PCr/ATP and Pi/PCr (p = 0.19). Using STEAM 31P-MRS at 7T we have for the first time explored Pi/PCr in the diabetic human heart and found it increased when compared to healthy controls. The lack of correlation between measured PCr/ATP and Pi/PCr suggests that independent mechanisms might contribute to these perturbations.